Penerapan Penerapan manajemen risiko pembiayaan pada lembaga keuangan - Aini, Mufidatul (Maliki Interdisciplinary Journal, 2026)
The growth of the financial services industry in Indonesia, encompassing banking, cooperatives, and financial technology (fintech), continues to face a fundamental challenge in the form of non-performing financing (NPF). This study aims to examine the implementation of financing risk management comprehensively in minimizing NPF, as well as to analyze its impact on financial stability and customer trust. Using a descriptive qualitative method with a literature study approach, this research explores the determinants of financing failure and mitigation strategies across financial sectors. The results indicate that NPF is driven by complex causal factors, including internal managerial issues, customer characteristics and socio-economic conditions, as well as macroeconomic fluctuations such as inflation and business cycles. To reduce these risks, financial institutions are required to implement an integrated risk management strategy through four essential stages: identification based on the 5C principles, exposure measurement, periodic monitoring, and control through the Three Lines of Defense framework. Furthermore, this study finds that in the digital landscape, weak credit scoring mechanisms in fintech lending may pose systemic risks to financial stability. In conclusion, the continuous integration of risk management is not only crucial for reducing non-performing financing ratios and safeguarding profitability, but also serves as a strategic instrument in maintaining customer loyalty and public trust in financial institutions.